ESG Leaders Index 2021–2023: ESG Disclosure, Capital Structure, and Profitability on Company Value - Sari, Siti Maulida; Hadi, Abdul; Sudirwo (Universitas Sulawesi Barat, 2025)
During the period 2021–2023, this study investigates the impact of ESG disclosure, capital structure, and profitability on company value listed in the ESG Leaders index. This quantitative research uses an associative problem formulation. The companies included in the ESG Leaders index are the subjects of this research. For this research, 17 companies were selected through a purposive sampling technique over three periods (2021–2023). Overall, 51 samples were taken for this study. This study uses multiple linear regression analysis conducted using the SPSS 23 program. The research shows that ESG disclosure decreases company value, profitability increases company value, and capital structure does not. These findings provide insights for practitioners and policymakers in managing ESG-related activities